Coincident Thyrotoxic Hypokalemic Periodic Paralysis and Cardiomyopathy - Steven Swarath MBBS; Nicole Maharaj MBBS; Arun Katwaroo MBBS; Valmiki Seecheran MBBS, MSc; Rajeev Seecheran MBBS, MHA; Priya Ramcharan MBBS, MRCP; Lakshmipathi Peram MBBS, MRCP; Naveen Seecheran MBBS (MD) (SAGE Publishing, 2024)
Thyrotoxic periodic paralysis (TPP) and thyrotoxic cardiomyopathy (TCMP) are potentially lethal complications of thyrotoxicosis that require emergent recognition and management to attenuate significant morbidity and mortality. We present the case of a 23-year-old Asian male with no prior medical history who developed TPP with coincident TCMP, which was successfully managed with antithyroid and heart failure therapies. The clinician should be aware of the diagnosis and treatment of these 2 life-threatening conditions in a hyperthyroid state.